Akuntabilitas Kinerja Dinas Perhubungan Kota Pekanbaru - Ukrimatul Umam; Zaili Rusli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
Performance accountability is a form of agency accountability for success or failure in carrying out the organization's mission to achieve the goals and objectives that have been set based on a system that is carried out periodically. Every government agency is required to compile a document of the Government Agency Performance Accountability System (SAKIP). In the implementation of accountability for the performance of the Pekanbaru City Transportation Service in 2017 and 2018 it received category C and in 2019 the Transportation Service received category B. This study aims to analyze the accountability of the Pekanbaru City Transportation Service's performance accountability and the factors inhibiting the performance accountability of the Pekanbaru City Transportation Service. This study uses the theory of Public Accountability by Ellwood in Nasucha (2004) consisting of four indicators, namely Honesty and Legal Accountability, Process Accountability, Program Accountability and Policy Accountability. This study uses a qualitative approach with descriptive analysis. In analyzing the data, this research uses triangulation technique. The results showed that the Pekanbaru City Transportation Service was accountable but still found the inhibiting factors, namely human resources related to administration and the lack of information disclosure related to performance.